Co-drug delivery of regorafenib and cisplatin with amphiphilic copolymer nanoparticles: enhanced in vivo antitumor cancer therapy in nursing care - Zhe Zhou (Taylor & Francis Group, 2020)
Cancers continue to be the second leading cause of death worldwide. Despite the development and improvement of surgery, chemotherapy and radiotherapy in cancer management, effective tumor ablation strategies are still in need due to high cancer patient mortality. Hence, we have established a new approach to achieve treatment-actuated modifications in a tumor microenvironment by using synergistic activity between two potential anticancer drugs. Dual drug delivery of Regorafenib (REGO) and Cisplatin (PT) exhibits a great anticancer potential, as REGO enhances the effect of PT treatment of human cells by providing stability of the microenvironment. However, encapsulation of REGO and PT fanatical by methoxypoly(ethylene glycol)-block-poly(D, L-lactic acid) (PEG-PLA in termed as NPs) is incompetent owing to unsuitability between the binary Free REGO and PT core and the polymeric system. Now, we display that PT can be prepared by hydrophobic coating of the dual drug centers with dioleoylphosphatidic acid (DOPA). The DOPA-covered PT can be co-encapsulated in PLGA NPs alongside REGO to stimulate excellent anticancer property. The occurrence of the PT suggestively enhanced the encapsulations of REGO into PLGA NPs (REGO-PT NPs). Further, the morphology of REGO NPs, PT NPs, and REGO-PT NPs and nanoparticle size was examined by transmission microscopy (TEM), respectively. Furthermore REGO-PT NPs induced significant apoptosis in human lung A549 and ovarian A2780 cancer cells by in vitro. The morphological observation and apoptosis were confirmed by the various biochemical assayes (AO-EB, Nuclear Staining and Annexin V-FITC). In a xenograft model of lung cancer, this nanotherapy shows a durable inhibition of tumor progression upon the administration of a tolerable dose. Our results suggest that a hydrophobic and highly toxic drug can be rationally converted into a pharmacologically efficient and self-deliverable nursing care of nanotherapy.Highlights Dual drug delivery of Regorafenib (REGO) and Cisplatin (PT) exhibits a great anticancer potential, as REGO enhances the effect of PT treatment of human cells by providing stability of the microenvironment. REGO-PT NPs induced significant apoptosis in human lung A549 and ovarian A2780 cancer cells by in vitro. The morphological observation and apoptosis were confirmed by the various biochemical assayes. In a xenograft model of lung cancer, this nanotherapy shows a durable inhibition of tumor progression upon the administration of a tolerable dose.